Mobile application to aid people with speech disorders - Basile, Felipe Rodrigues Martinêz; Silva, Diego Pereira da; Amate, Flávio Cezar (Journal of Health Informatics, 2014)
Nowadays information and communication technologies have been used to solve many health issues. Because of this, new studies are necessary to develop innovative tools in order to solve problems related to accessibility. The purpose of this paper is the development of an application for mobile devices, targeted to the Android platform, aiming to help people with disabilities to communicate. It is assumed that these people don’t have severe mobility issues, but have some of speech disorders. User interfaces and audiovisual features were created to improve the interaction between users and listeners with a total of 372 audiovisual features, considering 6 categories, 36 activities, 144 complementary phrases, along with 186 audio files. The result of this paper is the creation of new software to help people with speech disorders considering aspects of mobility and accessibility through the use of information and communication technologies.